Development of Vegetative Propagation Strategies for Balanites aegyptiaca in the Sahel, Niger - Moussa Massaoudou; Rabiou Habou; Zounon Christian Serge Félix; Abasse Tougiani; Patrick Van Damme (International Journal of Forestry Research)
Forests have always been a source of wood, food, and medicine for the rural populations of the Sahel. Anthropogenic and animal pressures often lead to low tree recruitment rates and seedling survival. Under certain conditions, multipurpose species such as Balanites aegyptiaca have shown dramatic decreases in population numbers. The objective of the present study is to determine the natural colonisation behaviour of B. aegyptiaca and to develop vegetative propagation strategies. Surveys were carried out in the agroforest parklands of the Regional Centre for Agricultural Research of Maradi Research Station. An inventory was carried out in 1,500 m2 plots to determine the species’ regeneration methods. We then tested seed germination success, and suckering induction, air-layering, and stem cuttings were carried out to determine the techniques best suited for the propagation of B. aegyptiaca. It emerged from this study that in nature, B. aegyptiaca is propagated naturally by dispersion of seeds (81.2%), as well as by rejection of the strain (13.5%) and by suckering (5.2%). The germination test showed that heavy seeds (38.4%) germinated best because they have a higher nutrient reserve. With a success rate of 11.1%, distal suckers react better than proximal suckers (5.5%) because they quickly acquire relative independence from the mother plant. As for air-layering, stems with large diameters react better (53.3%) than those with small diameters (46.6%) because they have thicker bark and store a large amount of elaborate sap responsible for rhizogenesis. In the stem segment cutting test, cuttings of small diameter react better at 30.8% than those of large diameter (12.6%) because they have a higher number of meristematic tissues. The stem segment cuttings seem to be the best adaptable alternative to the natural propagation of B. aegyptiaca because it combines ease of use, low cost, and a significant success rate.